2021
DOI: 10.3389/fpsyt.2021.553468
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: Demographic Predictors of Self-Isolation or Self-Quarantine and Impact of Isolation and Quarantine on Perceived Stress, Anxiety, and Depression

Abstract: Introduction: With the sudden onset and global dispersal of the SARS-CoV-2 virus, many nations including Canada attempted to reduce spread of the resultant COVID-19 syndrome with self-isolation and quarantine, while seeking a cure or vaccine for this disease. Understanding impacts of self-isolation and self-quarantine on stress, anxiety, and depression will help us to mitigate these issues through appropriate development of mental health services.Methods: The sample was drawn from individuals who self-subscrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 28 publications
3
56
1
1
Order By: Relevance
“…Furthermore, we found that male and married individuals are more likely to comply with quarantine guidelines than female, unmarried, or students of African origin. This finding is in line with those presented in the prior literature in which researchers showed that demographic characteristics may predict self-isolation behavior (Commodari and La Rosa, 2020;Nkire et al, 2021). Our study also found that essential knowledge about the disease is positively associated with self-quarantine.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we found that male and married individuals are more likely to comply with quarantine guidelines than female, unmarried, or students of African origin. This finding is in line with those presented in the prior literature in which researchers showed that demographic characteristics may predict self-isolation behavior (Commodari and La Rosa, 2020;Nkire et al, 2021). Our study also found that essential knowledge about the disease is positively associated with self-quarantine.…”
Section: Discussionsupporting
confidence: 93%
“…The study was a cross-sectional survey primarily aimed at collecting data on likely major depressive disorder and its relation to the COVID-19 pandemic. The survey included demographic, social, clinical and COVID-19-related variables and was adapted from survey questions used in Canada to gather baseline data from Text4Hope (a supportive text message program) subscribers during the COVID-19 pandemic [ 10 , 17 , 40 , 41 , 42 , 43 , 44 ]. Major depressive disorder symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9) [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The government of Ghana could adopt for the population mental health interventions such as Text4Hope, launched in Alberta, Canada during the start of the COVID-19 pandemic, which effectively reduced depressive symptoms and suicidal ideation in subscribers [ 41 , 74 , 75 , 76 ]. Supportive text message programs are cost-effective, geographic location independent, are free to the end user and do not require expensive data plans, can reach thousands of people simultaneously and have been used to support residents of Alberta, Canada in managing stress, anxiety and depression [ 44 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. A similar program could serve as a useful tool in Ghana and other low- and middle-income as well as high-income countries during the COVID-19 pandemic and also during natural disasters and other public health emergencies.…”
Section: Policy Implications and Future Directionsmentioning
confidence: 99%
“…We also observed that mental health conditions, including posttraumatic stress disorder, alcohol, tobacco and substance-use disorder, and sense diseases were associated with a lower risk of COVID-19. It is possible that those with these conditions were less likely to initiate tests for SARS-CoV-2, had difficulty reporting symptoms thus not captured as an infected person, or are more likely to self-isolate and thereby minimizing potential exposure [ 50 ]. However, due to the nature of our study design we cannot infer causality and only speculate the nature of the observed association.…”
Section: Resultsmentioning
confidence: 99%